FUNGSI DAN KEWENANGAN DEWAN PERWAKILAN RAKYAT SECARA KONSTITUSIONALITAS DALAM PENYELENGGARAAN NEGARA PASCA REFORMASI - Barlian, Iyan; Karsa, Pipih Ludia (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2023)
The administration of government, either in state power in the context of separation of powers (Separation Of Power), or division of powers (Distribution Of Power), the role of representative institutions participates with some of the functions and authorities it has. In Indonesia, the function of the House of Representatives has a Legislative Function, a Supervision Function, a Budget Function, all of which need synergy. Although its main function is legislation, its controlling function also needs to be effectively optimized in conducting supervision related to the implementation of government. As for the budget function, this will be related to the welfare of the people. While the authority or power based on the 1945 Constitution as a result of changes in the power of the DPR was enlarged including: The DPR is given the power to give consideration to the President in appointing Ambassadors and receiving ambassadors for the placement of other countries, providing amnesty and abolition, the DPR is also given power in the form of giving approval if the President wants to make agreements with other countries, whether in the economic sector, peace agreements,  declare war and other international treaties affecting territorial integrity. The DPR is also given budget rights, elects BPK members, by observing DPD advice, gives approval in the event that the President appoints or dismisses KY members and nominates 3 Constitutional Court judges. People's representation in representative institutions (DPR) can be said to be channeled if the interests of the values, aspirations, and opinions of the people represented have been fought for in the framework of people's welfare, both through the pattern of optimizing functions and the correlation of authority with other institutions